(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
تقوم هذه الدراسة على رصد محاولةٍ قائمةٍ على المزج بين ثلاثةِ حقول معرفيةٍ هي: الفلسفة والتاريخ والأدب، تتجلّى هذه المحاولة في سيرةِ علمٍ هو تاريخ الأفكار، يعدّ هذا العلم تتويجاً لتطور الحقلين الأولين؛ فالفلسفة تطوّرت مباحثها من (ما وراء الطبيعة)، إلى (نظرية المعرفة)؛ كما نتجت عنها علومٌ أخرى كعلم الاجتماع، وعلم الأخلاق. أمّا التاريخ فقد حافظ على ثباتٍ نسبي من حيث موضوعه، في تدوين أفعال البشر وسيرهم، حتى ظهرت فلسفة التاريخ التي تدرس الدوافع المثالية والبنى العليا الكامنة وراء أفعال البشر. أمّا الحقل الثالث أي الأدب فقد بقي مختبَراً لكل تطوّرٍ، فهو مسرحٌ لاختبار تفرعات الفلسفة، وعلى وجه التحديد مناهج البحث المختلفة المتضمنة في حقل وهو أيضاً وثيقةٌ يعتمدها المؤرخون في دراساتهم وأعمالهم في سير الأمم وأفعالها. إنّ ما تحاولُ الدراسة تقديمه هو نوعٌ آخر من الفلسفة الأدبية، وهو إلى ذلك نوع آخر من المقاربة الموضوعية للأدب لا تجعل الموضوع الأدبي هدفها بقدر ما تجعل الأفكار- الوحدات المكونة لهذه الموضوع غايتها، وهي لذلك تدرس الأدب وعينها على الفكر في حركيته وتطوره وتغيره، تدرسه في أكثر مسارحه اشتمالاً على تنوعه أي في الأدب، وتقوم في سبيلها إلى ذلك بكتابة نوع آخر من التاريخ هو تاريخٌ فرديٌّ منفصل عن التاريخ بشكليه الثابتين: الماورائي (الإلهي)، والمادّي ( الأرضي). This study is based on the monitoring attempt based on combining three fields of knowledge are: philosophy, history, literature, reflected this attempt in the biography of science is the science of the history of ideas, and this is science culmination of the evolution of the two fields the first two; philosophy evolved Mbagesha of (metaphysics), to ( theory of knowledge); also resulted in other sciences as a science meeting, and Ethics. As history has maintained relative stability in terms of subject matter, identify the actions of human beings and their curricula, until the appearance of the philosophy of history taught ideal motives and Supreme underlying structures behind human. The third field any literature has remained a laboratory for each development, it is the scene of test philosophy forest, and specifically different research methods included in the field who is also the document adopted by historians in their studies and their work in the course of nations and their actions . The Mathol study presented is another type of philosophy, literary, which to this type of approach substantive literature to Atjal Thread literary purpose as much Matjal ideas - the constituent units of this topic purpose, and therefore taught literature and the same thought in the dynamics and evolution and change, being studied in more Msarha inclusive diversity in literature, and are in the process of typing another kind of history is the history of an individual separate from the history Bashklah unwavering: metaphysician (divine), and material (ground).